One-stop shop for variceal surveillance: integration of unsedated ultrathin endoscopy into the routine clinic visit. Issue 7 (12th January 2021) - Eqbal, Ali; Wickremeratne, Tehara; Turner, Stephanie; Higgins, Sarah Elizabeth; Sloss, Andrew; Mitchell, Jonathan; O'Beirne, James
Abstract : Background: The endoscopic appearance of oesophageal varices determines the need for prophylaxis. However, as the point prevalence of varices is low (25%), the majority of surveillance endoscopies are unnecessary and costly. Narrow diameter, ultrathin (UT) endoscopes are more tolerable than conventional upper gastrointestinal (UGI) endoscopes and can be used without sedation. We hypothesised that unsedated UT endoscopy for variceal surveillance could be implemented during the routine outpatient clinic visit allowing accurate diagnosis of varices and the timely provision of prophylaxis. Methods: Patients with cirrhosis awaiting surveillance endoscopy were identified. UT endoscopy was scheduled during routine clinic review at the same time as ultrasound surveillance for hepatocellular carcinoma. UGI endoscopy was performed unsedated using the E.G Scan II disposable endoscope. Varices were graded using the modified Paquet classification. Video recordings of procedures were reviewed by blinded assessors and agreement was assessed using the kappa statistic. Results: 40 patients (80% male) underwent unsedated UT endoscopy. All procedures were successful and tolerated well in 98% of cases. Median procedure time was 2 min (IQR 1–3). Varices were found in 37.5% (17.5% grade 1 and 20% grade 2). Patients with grade 2 varices were prescribed non-selective beta blockers at the clinic appointment. Kappa statistic for the finding of any varices was 0.636 (p=0.001) and 0.8–1.0 for diagnosis of grade 2 varices (p<0.0001). Conclusions: Outpatient unsedated ultrathin endoscopy in patients with cirrhosis is accurate, safe and feasible. This integrative care model is convenient, particularly for regional communities, and is likely to result in significant cost savings associated with variceal surveillance.